The effect of perioperative fluid management and operative modifications on mortality and morbidity in patients undergoing pulmonary endarterectomy - YILDIZELİ, BEDRETTİN (My University, 2023)
© 2023, Sociedade Brasileira de Cirurgia Cardiovascular. All rights reserved.Introduction: Chronic thromboembolic pulmonary hypertension (CTEPH) is a severe disease treated with pulmonary endarterectomy. Our study aims to reveal the differences in liquid modalities and operation modifications, which can affect the patients’ mortality and morbidity. Methods: One hundred twenty-five patients who were diagnosed with CTEPH and underwent pulmonary thromboendarterectomy (PTE) at our center between February 2011 and September 2013 were included in this retrospective study with prospective observation. They were in New York Heart Association functional class II, III, or IV, and mean pulmonary artery pressure was > 40 mmHg. There were two groups, the crystalloid (Group 1) and colloid (Group 2) liquid groups, depending on the treatment fluids. P-value 0.05). Mean duration of stay in the intensive care unit (ICU) for Group 1 was 6.2 days and for Group 2 was 5.4 days (P>0.05). Readmission rate to the ICU for respiratory or non-respiratory reasons was 8.3% (n=4) in Group 1 and 11.7% (n=9) in Group 2 (P>0.05). Conclusion: Changes in fluid management have an etiological significance on possible complications in patient follow-up. We believe that as new approaches are reported, the number of comorbid events will decrease.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Surgery Medicine Sciences; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; TIP, GENEL & DAHİLİ; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; MEDICINE, GENERAL & INTERNAL; CARDIAC & CARDIOVASCULAR SYSTEMS; Cerrahi; Tıp (çeşitli); Kardiyoloji ve Kardiyovasküler Tıp; Surgery; Medicine (miscellaneous); Cardiology and Cardiovascular Medicine; Cardiopulmonary Bypass; Endarterectomy; Intensive Care Units; Morbity; Pulmonary Embolism; Thrombosis